The effect of the modified basic package of oral care on adolescent dental caries status in Zambia; a cluster randomized trial - Anthony, Severine N.; Mbawalla, Hawa S.; Kahabuka, Febronia K.; Siziya, Seter; Åstrøm, Anne N. (Frontiers in Oral Health, 2025)
BackgroundThe Basic Package of Oral Care (BPOC) was developed by the World Health Organization (WHO) in order to improve oral health care worldwide, yet evidence of its effectiveness is scarce. This study primarily assessed the outcome of applying modified BPOC on dental caries prevalence and secondarily on knowledge and behaviors related to dental caries among adolescents in Copperbelt Province, Zambia.MethodsA parallel arms cluster randomized field trial including 22 public secondary schools (11-intevention, 11-control) was carried out between January 2021 and March 2023 in Copperbelt Province, Zambia. A validated questionnaire collected data with respect to socio-demographics, knowledge, and dental caries-related behaviors. The caries assessment spectrum and treatment (CAST) instrument was used to examine the spectrum of carious lesions during the baseline, and the follow-up data collection phases. The 1st and 2nd follow up exams were conducted at 18 and 24 months after baseline, respectively. The intervention group received a six-month duration modified BPOC intervention while, the control group continued with their routine oral self-care. The analysis was based on the intention-to-treat protocol using generalized estimating equations (GEE), and the results were reported as OR (95% CI).ResultsOut of 1,794 participants at baseline, 1,690 (94.2%) and 1,597 (89.0%) were examined at the 1st and 2nd follow up intervals, respectively. Dental caries models showed significant interaction at 18 and 24 months [OR (95% CI) = 0.7 (0.6, 0.8), p < 0.001]. Adequate knowledge and use of fluoridated toothpaste models were the only secondary outcomes with significant interactions at 18 and 24 months follow up. Stratified analysis at 18 and 24 months showed that the intervention group had better outcomes for adequate knowledge, use of fluoridated toothpaste and dental caries.ConclusionThe modified BPOC was effective in reducing the prevalence of dental caries, improving knowledge on dental caries, and increasing the frequency of using fluoridated toothpaste among Zambian adolescents. Clinical Trial Registration[https://pactr.samrc.ac.za/TrialDisplay.aspx?TrialID=24046], identifier [PACTR202210624926299].